Analysis of the Influence of Economic Growth, HDI, Poverty, Income Inequality, and Covid-19 on Crime Rate in East Java - Fachrezi Adriansyah Ramadhan; Nugroho Suryo Bintoro (Journal of Development Economic and Social Studies, 2026)
This research discusses the influence of economic growth, HDI, and poverty on crime rates in East Java. The aim of this research is to find out whether economic growth, HDI, and poverty have an influence on crime rates in East Java. This research uses secondary data in the form of data Cross Section from 38 districts/cities and time series data from 2018-2022. The research is quantitative research with the method used, namely panel data regression analysis. This study shows that economic growth has a negative and significant effect on the crime rate. Meanwhile, the HDI and poverty variables have a positive and significant influence on crime rates. The result for the income inequality variable shows that income inequality has no influence on the crime rate. And in the Covid-19 variable, the results showed that Covid-19 had a significant negative effect on crime rates.